Removal of Cu(II) and Pb(II) Ions from Wastewater Solutions Using Black Soldier Fly (Hermetia illucens) Pupal Shell: Adsorption and Characterization - Eko Prasetyo Kuncoro; Azra Rhea Darmawati; Pramudya Lizza Roshita; Thin Soedarti (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
Industrial wastewater often contains heavy metals such as Pb(II) and Cu(II) that pose significant environmental and health risks. This study investigates the utilization of Black Soldier Fly (BSF) (Hermetia illucens) pupal shells as an adsorbent material for the removal of Pb(II) and Cu(II) ions from aqueous solutions. BSF pupal shells were chosen due to their high availability, rapid life cycle, and chitin-rich composition, making them suitable for heavy metal adsorption. The preparation process included washing, drying, grinding, and activation with 1 M NaOH solution. Characterization of the adsorbent was performed before and after adsorption using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy coupled with Energy Dispersive X-ray Spectroscopy (SEM-EDX). Adsorption experiments were conducted to examine the effects of pH, contact time, and initial ion concentration. The optimum pH for adsorption was found to be 5.5, achieving removal efficiencies of 95.5% for Pb(II) and 71.81% for Cu(II). The optimum contact times were 180 minutes for Pb(II) and 240 minutes for Cu(II). Kinetic analysis demonstrated that the adsorption process followed a pseudo-second-order model. Adsorption isotherm studies indicated that the Langmuir model provided a better fit (R² = 0.99 for Pb(II) and 0.98 for Cu(II)) compared to the Freundlich model (R² = 0.90 for Pb(II) and 0.77 for Cu(II)). These results demonstrate that BSF pupal shells are a promising, cost-effective, and environmentally friendly material for industrial wastewater treatment applications